Pelatihan Pembuatan Surat Izin Usaha sebagai bentuk legalitas UMKM - Maharani Putri; M. Syahruddin; Fitria Nova Hulu; Moh. Zainul Haq; Abdullah; Cholish (LPPM Universitas Al-Azhar medan, 2024)
Jelly Kelapa Kampung sub-district owners characterize East Binjai sub-district need a business license to get legality and legal protection from the government. However, Jelly Kelapa Kampung MSME business owners are still minimal in knowledge and mechanisms for making Business Identification Numbers (NIB) through Online Single Submission (OSS). This training activity aims to solve these problems by introducing, increasing knowledge, and assisting MSME owners Jelly Kelapa Kampung in making NIB through the OSS web. The implementation method used has 3 stages, namely socialization, training, and mentoring. The implementation of activities includes the submission of theory, making business licenses, and submitting business legality letters. The result of this activity is that the owner of Jelly Kelapa Kampung MSMEs shows increased knowledge about business legality and business registration into the OSS institution. Thus, MSME owners in Jelly Kelapa village get business protection, easy access to capital, empowerment from the government, and assistance for business development